Adopsi Sistem Pembayaran QRIS oleh UMKM: Studi Kasus pada Toko Afnan Parfum Samban - Gulo, April Elviyanti Dorothea; Maria Th, Alleta Dewi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article explores the perceptions and experiences of Micro, Small, and Medium Enterprises (MSMEs) at Toko Afnan Parfum Samban in adopting the digital payment system QRIS (Quick Response Code Indonesian Standard). The research focuses on the challenges and benefits faced by MSMEs, as well as their impact on customer experience and business performance. Using the technology adoption model theory, data were collected through semi-structured interviews with the owner and employees of Toko Afnan, as well as direct observations of the transaction processes. Data analysis was conducted qualitatively using a thematic approach to identify patterns emerging from the experiences of MSME actors. The results indicate that the use of QRIS provides significant benefits, including increased transaction efficiency and customer satisfaction, measured by a 30% increase in sales turnover after adoption. However, challenges such as a lack of technological understanding, doubts about security, and internet connectivity issues remain obstacles. This article compares the findings with case studies of other MSMEs in Indonesia and similar experiences in other countries, and it recommends strategic steps to improve digital literacy and technology accessibility. These findings provide important insights for stakeholders in supporting the adoption of digital payment systems among MSMEs.